True north discover your authentic leadership - George, Bill (William W.) (Warren Bennis signature series., 2007)
True North shows how anyone who follows their internal compass can become an authentic leader. This leadership tour de force is based on research and first-person interviews with 125 of today's top leaders -- with some surprising results. In this important book, acclaimed former Medtronic CEO Bill George and coauthor Peter Sims share the wisdom of these outstanding leaders and describe how you can develop as an authentic leader. True North presents a concrete and comprehensive program for leadership success and shows how to create your own Personal Leadership Development Plan centered on five key areas: a) knowing your authentic self; b) defining your values and leadership principles; c) understanding your motivations; d) building your support team; and e) staying grounded by integrating all aspects of your life. True North offers an opportunity for anyone to transform their leadership path and become the authentic leader they were born to be. -- Book jacket.